Fatores prognósticos de letalidade hospitalar por diarréia ou pneumonia em menores de um ano de idade: estudo de caso e controle Prognostic factors for hospital case-fatality due to diarrhea or pneumonia: a case-control study - Cora Luiza Araújo Post; Cesar Gomes Victora; Joaquim Gonçalves Valente; Maria do Carmo Leal; Flávia Maria Leal Niobey; Paulo Chagastelles Sabroza (Universidade de São Paulo, 1992)
Estudou-se a letalidade hospitalar devido à diarréia ou pneumonia em menores de um ano de idade na Região Metropolitana do Rio de Janeiro cujo óbito ocorreu entre abril/86 e maio/87. Foram investigados possíveis fatores prognósticos de letalidade hospitalar em relação a condições socioeconômicas, biológicas e amamentação aos 30 dias de vida. Foi utilizada metodologia de caso-controle, sendo casos as crianças internadas por diarréia ou por pneumonia que morreram, e controles aquelas que sobreviveram. Referências são feitas aos fenômenos de causalidade reversa e "overmatching" como possíveis viéses neste tipo de estudo. Razão de produtos cruzados (RPC) foi utilizada para estimar os riscos relativos, através de regressão logística não condicional. Os principais fatores prognósticos encontrados foram prematuridade, baixo peso ao nascer, mau estado geral e déficit peso/idade na hospitalização. Nas crianças com pneumonia a duração do aleitamento materno esteve associado com a letalidade (RPC=2,0). As condições biológicas evidenciaram-se como os principais fatores prognósticos de letalidade hospitalar por diarréia ou pneumonia. Diarrhea and pneumonia are common diseases in children aged under one year, for which there are simple therapeutic measures. However, infant mortality due to these diseases is still very high, varying markedly according to socio-economic status. The characteristics of children who died (cases) and of those who were hospitalized with diarrhea or pneumonia, but survived (controls), were studied. The following groups of variables were studied: socio-economic, environmental and biological conditions, nutritional status and breast-feeding. Information on cases and controls was collected from hospital records and through home interviews. Important losses occurred in the latter: 40% of cases and 50% of controls were not interviewed. There were no significant differences between cases who were included and those who were not, in terms of age, sex or place of residence. To estimate relative risks of prognostic factors unconditional Logistic Regression was used to calculate the odds ratios and their 95% confidence intervals. Prematurity, low birth weight, weight/age deficit, presence of edema and poor general status at hospital admission were prognostic factors for hospital case-fatality. In relation to the anthropometric variables, it was not possible to conclude for certain whether the increased case-fatality was linearly or non-linearly (threshold) associated with nutritional deficit. The duration of breastfeeding was only associated with case-fatality for pneumonia. Socio-economic factors were not important for the prognosis of children admitted to hospital with diarrhea or pneumonia. Some of the expected risk factor associations were not detected, maybe due to the small sample size (resulting from the high losses) which was insufficient to show small differences. In this study the biological conditions of children with diarrhea or pneumonia appeared to be the important prognostic factors for hospital case-fatality.